Case Report: Robotic PeTEP for Totally Extraperitoneal Repair of Incisional Hernia - Victor G. Radu (Journal of Abdominal Wall Surgery)
The development of minimally invasive surgical techniques for ventral hernias has significantly progressed, evolving from IPOM and IPOM + to advancements like eTEP/eTEP-TAR. These newer techniques have demonstrated their effectiveness by delivering excellent postoperative outcomes, despite being introduced less than a decade ago. Recreating traditional procedures, which are considered the “gold standard” in ventral hernia surgery, through minimally invasive methods—such as the Rives-Stoppa repair—could represent the next frontier in abdominal wall surgery. This publication focuses on replicating ventral incisional hernia repair using an extraperitoneal approach, as outlined by Todd Heniford, and taking inspiration from the PeTEP technique for primary ventral hernias, whether associated with diastasis recti or not, as described by Hector Valenzuela.